The Relevance of Values Education in Today’s Higher Education - Lakshmi, P. Selvarama (Journal of Research in Vocational Education, 2024)
Value education refers to the aspect of the educational practice which entails that moral or political values as well as norms, dispositions and skills grounded in those values are mediated to or developed among students. Concern for value education is increasing in recent years as a result of crisis of values that our society is currently experiencing. The issue has been projected as one of the national priority in the nations education. The paper remains a humble attempt at exploring the nature, purpose, methods and relevance of value education in higher education.